ST6GAL1 and α2-6 Sialylation Regulates IL-6 Expression and Secretion in Chronic Obstructive Pulmonary Disease - Krick, Stefanie; Helton, E. Scott; Easter, Molly; Bollenbecker, Seth; Denson, Rebecca; Zaharias, Rennan; Cochran, Phillip; Vang, Shia; Harris, Elex; Wells, James M.; Barnes, Jarrod W. (Frontiers in Immunology, 2021)
Chronic obstructive pulmonary disease (COPD) is a systemic disease strongly associated with cigarette smoking, airway inflammation, and acute disease exacerbations. Changes in terminal sialylation and fucosylation of asparagine (N)-linked glycans, have been documented in COPD, but the role that glycosyltransferases may play in the regulation of N-linked glycans in COPD has not been fully elucidated. Recent studies suggest that modulation of ST6GAL1 (ST6 beta-galactoside alpha-2,6-sialyltransferase-1), which catalyzes terminal α2-6 sialylation of cellular proteins, may regulate inflammation and contribute to COPD phenotype(s). Interestingly, it has been previously demonstrated that ST6GAL1, a Golgi resident protein, can be proteolytically processed by BACE1 (beta-site amyloid precursor protein cleaving enzyme-1) to a circulating form that retains activity. In this study, we show that loss of ST6GAL1 expression increased interleukin (IL)-6 expression and secretion in human bronchial epithelial cells (HBECs). Furthermore, exposure to cigarette smoke medium/extract (CSE) or BACE1 inhibition resulted in decreased ST6GAL1 secretion, reduced α2-6 sialylation, and increased IL-6 production in HBECs. Analysis of plasma ST6GAL1 levels in a small COPD patient cohort demonstrated an inverse association with prospective acute exacerbations of COPD (AECOPD), while IL-6 was positively associated. Altogether, these results suggest that reduced ST6GAL1 and α2-6 sialylation augments IL-6 expression/secretion in HBECs and is associated with poor clinical outcomes in COPD.